A fuzzy logic based driver fatigue detection system - Pour, Kamran Mohammad; Menhaj, Mohammad Bagher; Davoudi, Mohsen (SAE International, 2007)
In this paper, we explain the process of designing fuzzy based analyzers which can be installed in a vehicle. These analyzers use some kinds of sensors to detect the driver fatigue. This system helps a driver to be alert during vehicle driving. We propose a fatigue detection method which works in different way from the previous systems. In this method using some tactile sensors, the system predicts fatigue before the driver falls asleep, while driver's alertness and reaction decreases and the probability of the accident increases. An alarm massage concentrates the driver attention while s/he is going to be fallen in sleep. An advantage of this kind of fatigue detection is that it doesn't interfere with the driver's habit in vehicle control and it resumes functioning only in critical moments. © @ 2007 SAE International.
Commercial Vehicle Engineering Congress and Exhibition --
Keywords: Automobiles; Automotive engineering; Control system synthesis; Fuzzy logic; Critical moment; Driver attention; Driver fatigue; Fatigue detection; Tactile sensors; Vehicle Control; Commercial vehicles